A Comparative Analysis of Laser-Ablated Surface Characteristics Between the Si Face and C Face of Silicon Carbide Substrates - Hsin-Yi Tsai; Yu-Hsuan Lin; Kuo-Cheng Huang; J. Andrew Yeh; Yi Yang; Chien-Fang Ding (Micromachines)
Silicon carbide (SiC) has significant potential as a third-generation semiconductor material due to its exceptional thermal and electronic properties, yet its high hardness and brittleness make processing costly and complex. This study introduces ultraviolet laser ablation as a method for direct SiC material removal, investigating the effects of varying scanning speeds on surface composition, hardness, and ablation depth. The results indicate optimal processing speeds for the Si and C faces at 200 mm/s and 100 mm/s, respectively. Ablation depth is linearly correlated with laser repetitions, achieving a 25% improvement in removal efficiency at 100 mm/s on the C face compared to higher speeds. A composition analysis shows that the Si and C faces of SiC exhibit consistent ratios of Si, O, and C both before and after ablation. Post-ablation, the proportion of Si and C decreases with an increased presence of oxygen. At scanning speeds below 200 mm/s, the variation in speed has minimal effect on the compositional ratios, indicating a stable elemental distribution across the surface despite differences in processing speed. Hardness testing indicates an initial hardness of 13,896 MPa for the C face, higher than that of the Si face, with both surfaces experiencing a drop to less than 1% of their original hardness (below 50 MPa) after ablation. Lattice structure analysis shows Moissanite-5H SiC and cubic silicon formation on the Si face, while the C face retains partial SiC structure. This study found that when laser parameters are used to process SiC, the processing parameters required on both sides are different and provide important reference information for future industrial processing applications to shorten the time and process cost of SiC surface thinning.